G412 Assessment of asymptomatic neonates referred from the postnatal ward with a murmur in a dedicated registrar murmur clinic is a safe, effective way to screen prior to echocardiographic assessment. (24th May 2017) - Wacher, JL; Edgington, C; Sigdel, D; Webster, A; Rose, K; Banerjee, J
Abstract : Aims: Prior to April 2016 neonates with an asymptomatic murmur that persisted past 24 hours on the postnatal ward in our centre were referred for outpatient echocardiogram. Unfortunately due to staff changes in our echocardiography department we were no longer able to offer this service. A new pathway was introduced where these babies were reviewed in a dedicated Registrar mumur clinic, ideally within 10 days, prior to assessment by a Neonatologist with expertise in cardiology including echocardiogram. We hypothesised that this would reduce the number of babies referred for echocardiogram. Methods: The electronic records of all babies seen in the registrar murmur clinic between April 2016 and December 2016 were reviewed and the following data collected: Length of time between referral to clinic and date of clinic appointment offered, outcome of the murmur clinic appointment, length of time between murmur clinic appointment and echocardiographic assessment, and the outcome of those undergoing echocardiographic assessment. Results: A total of 178 murmur clinic appointments were reviewed. 26 were excluded for being repeat appointments for DNA's or for being inappropriately booked into murmur clinic. Of 152 individuals assessed in murmur clinic the median time to appointment from referral was 14 days. 52 (34%) had a persisting murmur and were referred for echocardiogram. The median time between echocardiogram and murmur clinic was 48 days. 11 (7%) seen for echocardiogram had findings consistent with congenital heart disease. None of the babies discharged directly from murmur clinic re-presented to our unit with congenital heart disease. Conclusions: We reduced the number of referrals to a consultant clinic for echocardiogram by 66% without missing any incidences of congenital heart disease, showing that a dedicated registrar murmur clinic is a safe cost effective way to screen babies with a murmur. We are currently streamlining the referral and admin process and hope to reduce waiting times and inappropriate clinic booKing's. We postulate with a reduced number of postnatal ward referrals the waiting time for echocardiogram will reduce. We will be collecting data for patients seen between January and March 2017 and hope to show an improvement in the waiting times for echocardiogram.